2014
DOI: 10.7554/elife.02324
|View full text |Cite
|
Sign up to set email alerts
|

Expression site attenuation mechanistically links antigenic variation and development in Trypanosoma brucei

Abstract: We have discovered a new mechanism of monoallelic gene expression that links antigenic variation, cell cycle, and development in the model parasite Trypanosoma brucei. African trypanosomes possess hundreds of variant surface glycoprotein (VSG) genes, but only one is expressed from a telomeric expression site (ES) at any given time. We found that the expression of a second VSG alone is sufficient to silence the active VSG gene and directionally attenuate the ES by disruptor of telomeric silencing-1B (DOT1B)-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 41 publications
7
120
0
Order By: Relevance
“…Another recent report demonstrated that a VSG, transcribed at a chromosomeinternal site by T7-phage polymerase, transiently silenced the native VSG (25). This same report demonstrated repression spreading along the VSG-ES in a DOT1B, histone methyltransferase-dependent manner (25). Spreading of a repressed domain may also explain why we see derepression of both bicistronic GFP and NPT reporters during VEX1 knockdown (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Another recent report demonstrated that a VSG, transcribed at a chromosomeinternal site by T7-phage polymerase, transiently silenced the native VSG (25). This same report demonstrated repression spreading along the VSG-ES in a DOT1B, histone methyltransferase-dependent manner (25). Spreading of a repressed domain may also explain why we see derepression of both bicistronic GFP and NPT reporters during VEX1 knockdown (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…We now show that this repression is VEX1-dependent and also that homologous sequences can promote VEX1-dependent repression. Another recent report demonstrated that a VSG, transcribed at a chromosomeinternal site by T7-phage polymerase, transiently silenced the native VSG (25). This same report demonstrated repression spreading along the VSG-ES in a DOT1B, histone methyltransferase-dependent manner (25).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It has recently been proposed that antigenic variation is linked with differentiation in T. brucei [44,45]. Overexpression of a second ectopic VSG from an inducible promoter can result in transient silencing of the active ES proceeding upwards from the telomere.…”
Section: How Is Vsg Expression Controlled In a Monoallelic Fashion?mentioning
confidence: 99%
“…This monoallelic VSG expression ensures that after a VSG switching event, the originally active VSG no longer is expressed on the cell surface. Several mechanisms of VSG expression regulation have been identified, including specialized localization of the active ES at an extranucleolar ES body (ESB) that is enriched with RNA polymerase I (24), regulated transcription elongation along ESs (25,26), modulation of ES chromatin structure (27)(28)(29)(30)(31)(32), modulation of ES promoter activities (33)(34)(35)(36)(37), and telomere protein-mediated telomeric silencing (38,39). VSG expression regulation has been reviewed elsewhere recently (40, 41) and will not be discussed here in detail.…”
Section: Antigenic Variation In T Bruceimentioning
confidence: 99%